2019
DOI: 10.1111/anec.12643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short‐term fasting on electrocardiographic parameters

Abstract: IntroductionDuring early drug development trials, electrocardiograms (ECGs) in healthy volunteers who are in a fasting state are evaluated to screen for possible adverse cardiac effects. However, the effect of the duration of fasting on electrocardiographic parameters is largely unknown. We compared the effects of fasting on standard 12‐lead electrocardiographic recordings.MethodsElectrocardiograms were available for 432 healthy subjects (mean age 28.5 ± 12.5; 88.9% male) who participated in early drug develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
1
1
Order By: Relevance
“…Additionally, the presence of transient ER pattern, QRS shortening as well as decreased HR have been reported in subjects with food deprivation [ 32 , 33 ]. The substantial impact of fasting on ECG parameters with a certain intersubjective variability of physiological response by food intake, demonstrated in previous research [ 30 ], can be confirmed by our data on ECG parameter changes. In this context, our obtained findings in healthy subjects demonstrated the safety of various fasting interventions with no clinically relevant ECG parameter changes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, the presence of transient ER pattern, QRS shortening as well as decreased HR have been reported in subjects with food deprivation [ 32 , 33 ]. The substantial impact of fasting on ECG parameters with a certain intersubjective variability of physiological response by food intake, demonstrated in previous research [ 30 ], can be confirmed by our data on ECG parameter changes. In this context, our obtained findings in healthy subjects demonstrated the safety of various fasting interventions with no clinically relevant ECG parameter changes.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies in healthy individuals demonstrated no increased cardiac risk during body mass reduction by the modified fasting intervention of moderate duration [ 28 ] and unaltered ECG following the fastening condition [ 29 ]. Contrary findings were revealed previously which analyzed the influence of brief and transient fasting on ECG parameters as well as HRV data, whereas decreased measurements for QRS duration, baseline HR and changes in QTc duration as well as HRV alterations could be revealed [ 27 , 30 , 31 ]. Additionally, the presence of transient ER pattern, QRS shortening as well as decreased HR have been reported in subjects with food deprivation [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation